Disablity Wellnes Center sebagai Upaya Penunjang Kesehatan kaum Disabilitas di Kabupaten Gianyar : bahasa indonesia - Wayan Aria Bayu Daniswara; Gde Bagus Andhika Wicaksana; I Nyoman Nuri Arthana; Made Anggita Wahyudi Linggasani (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Currently there are still many people with disabilities experiencing problems in receiving treatment and training, especially on the island of Bali. There is also another issue that is developing that there are still many persons with disabilities who have not received mental and physical health, and even if there is access to mental and physical health, there are still many who have not implemented disability access and there is also no wellness center designated for persons with disabilities. The design of the Disability Wellness Center located in Tampaksiring District, Gianyar Regency aims to provide a wellness center for persons with disabilities to help persons with disabilities obtain mental and physical health services. The choice of the location for the Tampaksiring District is because the location of this site is a tourism route, so that in addition to obtaining services at the Disability Wellness Center, persons with disabilities can also enjoy traveling in the tourism area near the site location. Keywords: Disability Wellness Center, Disability, Gianyar